Postpartum psychiatric disorders (Archives of Clinical Psychiatry, 2010)
OBJECTIVE: The postpartum period is marked by biological, psychological and social changes. Women are considered most susceptible to psychiatric disorders during the postpartum period. Puerperal blues, postpartum depression and postpartum psychosis have been classically associated to the postpartum. Anxiety disorders have also recently been associated to this period. METHOD: The present article reports a review of the literature on postpartum psychiatric disorders based on articles found on the PubMed and SciELO databases, published between 2000 and 2009. Relevant books, theses and other articles cited in the articles found were also included in this review. RESULTS: Puerperal dysphoria occurs in 50% to 85% of women following childbirth and is typically mild and transient in nature and requires no treatment. Postpartum depression has a prevalence rate of around 13% and can have negative repercussions on mother-infant interaction and other life events and must therefore be treated. Postpartum psychosis is rare, occurring in approximately 0.2% of puerperium cases. This condition is severe with psychotic and affective symptoms as well as risk of suicide and infanticide. Postpartum psychosis patients generally require hospital treatment. Anxiety disorders may be exacerbated or precipitated during the postpartum, particularly generalized anxiety disorder, post-traumatic stress disorder and compulsive-obsessive disorder. DISCUSSION: Although not recognized as distinct diagnostic entities under current classification systems, mental disorders during the puerperium present clinical features which warrant the attention of clinicians and researchers.